Factors that influence choice of contraception at mid trimester termination of pregnancy at Groote Schuur Hospital vs. New Somerset Hospital, Cape Town - Klassen, Thalia (Department of Obstetrics and Gynaecology, 2022)
Background: Little is known about factors which influence women's attitudes toward and choice of contraception following mid-trimester termination of pregnancy. Contraceptive counselling is part of the work-up and is an essential part of the documentation required by the department of health. Aim: To investigate the motivation behind the contraceptive choice in those women who present for a mid-trimester termination of pregnancy presenting to Groote Schuur Hospital and New Somerset Hospital and to see if there were any differences in the choice of contraception between these two groups of women Methods: We interviewed women accessing mid-trimester TOPs at two state hospitals within the Cape Town West Metropole using a purpose built non-validated, qualitative questionnaire for the purpose of this study. Findings: The injectable was the most used contraceptive method before TOP and LARCS were more utilized after TOP. Duration of action of methods and personal preference were what motivated the choice of contraception for most women in this study with no statistically significant difference between the two groups. Women in this study did not indicate that counselling influenced their choice. However, there was an eight-fold increase in the uptake of LARCS post TOP. Knowledge of its long duration of action was the motivating factor for choosing a LARC and this information would have been imparted during the counselling process. Women who underwent a medical TOP were more likely to choose an injectable contraceptive whereas women who underwent surgical TOPs chose the IUCD. Delay to diagnosing pregnancy and decision to TOP where reasons for TOP being delayed to the mid trimester. Conclusion: Counselling provided at TOP, positively impacted women's contraceptive choices, improving the uptake of highly effective contraceptive methods. Stronger sexual education programmes that teach young women about their menstrual cycles, contraception and how to prevent unintended pregnancies needs to form part of basic education core curriculums as well as primary health care programmes. Negative staff attitudes towards this essential service needs to be addressed.